(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Zhigir V. I. The administrative competence as a necessary condition of professionalism of manager of education. The article is devoted to the problem of forming of administrative competence of manager of education as a necessary condition of his professionalism. The approaches to the determination of concept are examined here, the structure of administrative competence of manager of education is also opened up. The features of economic, systematic-forecasting, strategic, organizational, supervisory, information-analytical components of administrative competence of manager of education are described.